Effects of Age at Entry, Knowledge Intensity, and Imitability on International Growth - Autio, Erkko; Sapienza, Harry J.; Almeida, James G. (Academy of Management Journal, 2000)
We employed knowledge-based theory to shed light on international growth in entrepreneurial firms. We found earlier initiation of internationalization and greater knowledge intensity to be associated with faster international growth. However, contrary to expectations, firms with more imitable technologies also grew faster. The former results suggest that early pursuit of international opportunity induces greater entrepreneurial behavior and confers a growth advantage, whereas the latter call into question current views of the role of imitability in international growth.